2001
DOI: 10.1046/j.1365-2648.2001.01785.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a theoretical framework describing relatives’ involvement in palliative care

Abstract: An important conclusion that can be of importance in palliative care is that the manner in which the staff act toward the patient and relatives influence relatives' possibilities for involvement, patients' possibilities for an appropriate death, and the possibilities the staff have to give good care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
122
0
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(133 citation statements)
references
References 13 publications
7
122
0
4
Order By: Relevance
“…The main picture that emerged from the analyses concerned comfort, retaining everyday life, action, commitment, hope, self-transcendence, and doing the best possible. The significance of these aspects is supported by other studies of next of kin of palliative patients during ongoing care~Brown et al Hull, 1990;Steele & Fitch, 1996;Andershed & Ternestedt, 2001;Grbich et al, 2001;Strang & Strang, 2001!, of palliative patients~Cameron & Parkes, 1983Salander et al, 1996;Hodgson et al, 1997;Breitbart, 2002!, in the general palliative or coping literature~Lazarus & Folkman, 1984;Doyle & Jeffrey, 2000;Kinsella et al, 2000!. However, few previous studies have focused specifically on meaningfulness for next of kin of patients in palliative home care, and the present study revealed aspects that have not been much illuminated in earlier literature and that seem important for the clinical situation.…”
Section: Discussionmentioning
confidence: 81%
“…The main picture that emerged from the analyses concerned comfort, retaining everyday life, action, commitment, hope, self-transcendence, and doing the best possible. The significance of these aspects is supported by other studies of next of kin of palliative patients during ongoing care~Brown et al Hull, 1990;Steele & Fitch, 1996;Andershed & Ternestedt, 2001;Grbich et al, 2001;Strang & Strang, 2001!, of palliative patients~Cameron & Parkes, 1983Salander et al, 1996;Hodgson et al, 1997;Breitbart, 2002!, in the general palliative or coping literature~Lazarus & Folkman, 1984;Doyle & Jeffrey, 2000;Kinsella et al, 2000!. However, few previous studies have focused specifically on meaningfulness for next of kin of patients in palliative home care, and the present study revealed aspects that have not been much illuminated in earlier literature and that seem important for the clinical situation.…”
Section: Discussionmentioning
confidence: 81%
“…The ways in which palliative care providers interact with relatives profoundly influence their ability for involvement (see also Andershed & Ternestedt, 2001). It has been argued that relatives' emotions around participation in care, and satisfaction with their own contributions, constitute important memories after the death of the loved one (Brown & Stetz, 1999;Grbich, Parker, & Maddocks, 2001;Koop & Strang, 2003;Milberg, 2003).…”
Section: Discussionmentioning
confidence: 97%
“…Studies have demonstrated the importance for relatives of dying patients to be given sufficient information about the patient's situation, to be involved in the patient's care and to be offered support for their own difficult situation [34][35] Eriksson & Lauri [36] pointed out that relatives' need for information was greater than their need for emotional support, which also emphasizes the importance of communication goals [6,7]. Insufficient acknowledgement was described by patients in terms of insufficient respect and not being seen as a unique person.…”
Section: Discussionmentioning
confidence: 99%